Telaah Kritis Dinamika Ortopedagogik - Zainur Arifin (Muróbbî: Jurnal Ilmu Pendidikan, 2018)
Orthopedagogics are often divided into two types, general orthopedagogics with regard to education for exceptional children in general, while special orthopedagogics regarding education for each type of child is extraordinary. Orthopedicagogics provide educational services as well as ordinary educational goals, but of course with some adjustments according to the abilities of extraordinary children. Objectives that are beyond the child's ability need not be conveyed. Orthopedagogic education as a science that has a very broad scope, because in it there are many aspects or parties that are involved either directly or indirectly. Likewise orthopedagogics in which education has the same scope, only all aspects of the scope are adjusted to the needs of orthopedagogic students. The development of community attitudes towards children with special needs is divided into four phases of development, phases of neglect, the phase of protection, the phase of education, and the phase of self-development for children with special needs. Children with special needs have the tendency to give up easily when they feel they cannot or cannot survive so that they are in an inferior position. Therefore, education has an important role to overcome inferiority, build the ability to adapt, have skills and not have dependence on others.